Prevalence and correlates of fear of falling among elderly population in urban area of Karnataka, India - Abhay B Mane; T Sanjana; Prabhakar R Patil; T Sriniwas (Wolters Kluwer Medknow Publications, 2014)
Context: Falls are a major public health problem in the elderly population. Fear of falling (FOF) among elderly persons can compromise quality of life by limiting mobility, diminished sense of well-being and reduced social interactions. India is undergoing a demographic transitional phase with urban elderly population of 6.72% in 2001. The major challenge would be on the prevention of falls among them. Hence there is a need to highlight the problems related to fall faced by the elderly in India. Objective: To study the prevalence of FOF and its correlates among the elderly population in urban area. Materials and Methods: 250 elderly subjects above 60 years were randomly selected from urban area and interviewed for FOF using Short Fall Efficacy Scale-I (FES-I) , history of falls and risk factors. Results: The prevalence of FOF among the elderly was 33.2%. The significant correlates of FOF were educational status, family type, associated health problems, history of fall in past 6 months, worried of fall again among fallers, fearfulness of fall again among fallers, restriction of daily activities and depression among them. The insignificant correlates were gender and socio-economic status. Conclusion: FOF is a health problem among the elderly living in urban India needs urgent attention. It represents a significant threat to socialization, independence and morbidity or mortality. Knowledge of correlates of FOF may be useful in developing multidimensional strategies to reduce it among elderly.